1997
DOI: 10.1007/s004360050336
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide involvement in experimental Trypanosoma cruzi infection in Calomys callosus and Swiss mice

Abstract: Nitric oxide (NO) production by peritoneal macrophages was evaluated in Calomys callosus and Swiss mice during the course of infection with two strains of Trypanosoma cruzi. In C. callosus, no NO production was detected throughout the period of observation in animals infected with either parasite strain, except for a very low amount measured on day 40 in animals infected with strain M226 and on the 28th day in animals infected with strain F after in vitro stimulation with interferon gamma (IFN-gamma). Macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Studies in vitro showed the mediation of TNF and INF-g in the resistance to T. cruzi infection in both human (Muñoz-Fernańdez et al, 1992a) and mouse macrophages (Silva et al, 1995) by increased NO production. Another report in vivo infections showed that the production of NO was host-dependent (de Oliveira et al, 1997). Macrophages from mice deficient in the expression of IFN-g receptor and iNOS showed impaired trypanocidal activity of macrophages (Hölscher et al, 1998).…”
Section: Host-derived Rns and Ros In Trypanosoma Cruzi Infectionmentioning
confidence: 99%
“…Studies in vitro showed the mediation of TNF and INF-g in the resistance to T. cruzi infection in both human (Muñoz-Fernańdez et al, 1992a) and mouse macrophages (Silva et al, 1995) by increased NO production. Another report in vivo infections showed that the production of NO was host-dependent (de Oliveira et al, 1997). Macrophages from mice deficient in the expression of IFN-g receptor and iNOS showed impaired trypanocidal activity of macrophages (Hölscher et al, 1998).…”
Section: Host-derived Rns and Ros In Trypanosoma Cruzi Infectionmentioning
confidence: 99%